Analysis of Lithology Influence on the Coliform Distribution in Semarang City - Umar, Savikri Misbahul; Putranto, Thomas Triadi; Pangestuti, Dina Rahayuning; Susanto, Novie; Santi, Narulita (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The amount of available water is becoming more scarce due to increased human demand. As a result, people are now obtaining their water from limited aquifers or deep groundwater from artesian water sources. Nonetheless, the varied properties of the soil and rocks within it do not ensure that the groundwater's quality remains safe from microorganisms or germs. Coliform, one of the bacteria or microorganisms that can increase in groundwater due to variations in the rock lithologies found in different regions. Analysis of coliform bacteria distribution was carried out in 30 drilled wells from confined aquifers spread across the city of Semarang. This research identified total coliforms using the Most Probable Numbers (MPN) method. The presence of coliform bacteria in certain wells was compared with the characteristics of rocks, where in this study area there are several rock lithologies such as volcanic breccia, andesite, pyroclastic breccia, lava, and clay. As for the results of this analysis, it was found that 10% of the samples contained total coliforms that exceeded the maximum limit of 50 CFU/100 ml, where the lithology with the highest total coliform content was found in the basalt area with the highest results, namely TNTC (Too Numerous to Count).